PENGEMBANGAN BAHAN AJAR AKUNTANSI PADA MATERI PERSAMAAN AKUNTANSI - Khalimatul Fajariyah, (Pendidikan Ekonomi, 2011)
The research is intended to develop a learning material in Accounting Equation, to describe the suitability of the material with assessment criteria issued by BSNP, and to describe the students response to the learning material. The research uses four D model, but confined to the level develop. The data collection techniques were validation sheets of learning materials and questionnaire of students response. The result shows that the learning material has already met the criteria up to 61 % in terms of content and presentation. The students responded positively to the content and presentation suitability of the learning material.